Penelitian Pembelajaran Bahasa Arab Secara Daring pada Masa Pandemi Covid 19 di Indonesia - Idris, syarifuddin (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Several studies related to the implementation of online Arabic learning during the Covid-19 pandemic in Indonesia have been carried out in Indonesia and published in national journals. However, there has been no survey of articles related to research on the implementation of online Arabic learning during the Covid-19 pandemic in Indonesia. Thus, this research aims to classify all the research results into several categories related to research on the implementation of online Arabic learning during the Covid-19 pandemic in Indonesia. This research utilizes the Systematic Literature Review (SLR) method which is used to identify research results on the topic of implementing online Arabic learning during the Covid-19 pandemic in Indonesia. This research data comes from 6 articles that have been accredited by the Ministry of Research, Technology and Higher Education of the Republic of Indonesia and 1 article that has been presented at an Arabic conference. The results of this research map factual information related to the opportunities and challenges experienced by educators and students in implementing online Arabic learning during the Covid-19 pandemic. This research can also be used as a reference in further research on the implementation of Arabic learning.